The role of bacteriophages in shaping bacterial composition and diversity in the human gut - Alkhalil, Samia S. (Frontiers in Microbiology, 2023)
The microbiota of the gut has continued to co-evolve alongside their human hosts conferring considerable health benefits including the production of nutrients, drug-metabolism, modulation of the immune system and playing an antagonistic role against pathogen invasion of the gastrointestinal tract (GIT). The gut is said to provide a habitat to diverse groups of microorganisms where they all co-habit and interact with one another and with the immune system of humans. Phages are bacterial parasites that require the host metabolic system in other to replicate via the lytic or the lysogenic cycle. The phage and bacterial populations are regarded as the most dominant in the gut ecosystem. As such, among the various microbial interactions, the phage-bacteria interactions although complex, have been demonstrated to co-evolve over time using different mechanisms such as predation, lysogenic conversion and phage induction; alongside counter-defence by the bacterial population. With the help of models and dynamics of phage-bacteria interactions, the complexity behind their survival in the gut ecosystem was demystified and their roles in maintaining gut homeostasis and promoting the overall health of humans were elucidated. Although the treatment of various gastrointestinal infections has been demonstrated to be successful against multidrug-resistant causative agents, still concerns about this technique are very much alive among researchers owing to the potential of phage to evolve. Since a dearth of knowledge exists regarding the use of phages for therapeutic purposes, more studies involving experimental models and clinical trials are needed to widen the understanding of bacteria-phage interactions and their association with immunological response in the gut of humans.